Difference in quality of preparates of mice kidney histology using xylol and sunflower oil (Helianthus annuus) on deparafinization processes - Adin Bhagawanti Poernomo; Juliana Christyaningsih; Ratno Tri Utomo; Wisnu Istanto (International Journal of Advanced Health Science and Technology, 2025)
ematoxylin-Eosin staining begins with deparaffinization. Deparaffinization aims to remove the remaining paraffin in the tissue and xylol is a commonly used deparaffinization material but the use of xylol has a bad impact on health and also the environment because of its toxic nature besides the price of xylol is relatively more expensive. A more natural material that is not harmful to the body and the environment is needed as an alternative to xylol. Sunflower oil is a type of vegetable oil that contains oleic acid. The oleic acid content in sunflower oil has a chain of carbon atoms that is non-polar and water insoluble so that it can dissolve paraffin which is non-polar and hydrophobic. This study was conducted at Faculty of Veterinary Medicine Airlangga University, Veterinary Farm Center and the Cytohistotechnology Laboratory of the Medical Laboratory Technology Department of the Surabaya Ministry of Health Polytechnic also this study was conducted from January - May 2025. which examined the differences in the quality of mice kidney histology preparations using xylol and sunflower oil in the deparaffinization process with experimental research methods and the sample size obtained using the federer formula was 24 preparations and divided into 4 groups including xylol, sunflower oil at 50oC for 5 minutes, 10 minutes and 15 minutes. The data were statistically processed with the Kruskal Wallis non-parametric test and the results showed that Ho was accepted (P = 0.350) so it can be concluded that there is no significant difference between the preparations deparafinitation with sunflower oil and xylol in hematoxylin eosin